Вычислите : пожайлуста только с подробным объяснением

(√3+2√2)+(√3-2√2+√2)

2

2

Ответы и объяснения

  • AlbuRin
  • светило науки
2013-07-14T12:49:40+04:00

((v3  +  2v2)  +  (v3  -   2v2  +  v2)) / v2  =  (2v3  +  v2)/v2  =  2v3/v2  +  v2/v2  =  v6  +  1

  • Участник Знаний
2013-07-14T12:57:17+04:00

V 3 = A                  V 2 = B

1) ( A + 2B) \ B 

2) (A - 2B + B) \ B = (A-B) \ B

3) (A + 2B + A - B) \ B = (2A + B) \ B 

4) (2V3 + V 2) \ V 2 = (V 12 + V 2 ) \ V 2 

5) (3.46 + 1.41) \ 1.41 = 4.87 \1.41 = 3.45